Fish Oil Substitution in Fish Feed Using Vegetable Oils, Terrestrial Animal Fats and Indonesian Local Raw Material Candidates (A Review) - Thoy Batun Citra Rahmadani; Wastu Ayu Diamahesa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Aquaculture is one of the world's most rapidly expanding producers of protein-rich diets. This is in accordance with the rising demand for feed to sustain these activities. However, the use of natural materials for fish feed, particularly fish oil, creates a paradox because it is derived from fish, therefore it is against the principles of sustainable agriculture. This article examines vegetable oils with a superior nutritional profile, palatability, digestibility, anti-nutritional factors, availability, and cost in comparison to fish oil. The ten-year-old articles selected and compiled originate from national (SHINTA) and international (Elsevier and Proquest) websites. Finding alternatives to fish oil as a source of lipids in fish diets is the result of several decades of research. Vegetable and animal sources are two main types of fish oil substitutes. Up to one hundred percent of fish oil can be substituted with vegetable oils like palm oil, canola oil, soybean oil, and olive oil. Similarly, animal sources can provide up to 75% of the lipids necessary for fish diets. Moreover, rubber seed oil has the potential to supplant fish oil in Indonesia due to its high omega-3 fatty acid content, which is comparable to that of fish oil. The conclusion of this review is that there are multiple sources of lipids that can be used to replace fish oil, and that more consideration must be given to the type of lipid source used in accordance with the type of fish being cultivated and the location of the fish cultivation.